Raising Righteous Children: A Qualitative Inquiry into Prophetic Parenting Principles in Contemporary Muslim Families - Hilyah Farhany Faradilla (Islamic Counseling and Parenting Journal, 2025)
This qualitative study explores how contemporary Muslim families implement Prophetic parenting principles to nurture righteous children amidst modern challenges. Against the backdrop of global concerns about moral decline and the erosion of religious values in youth, the research examines how Islamic child-rearing traditions adapt to contemporary contexts. The study addresses three key objectives: (1) identifying core Prophetic parenting principles practiced today, (2) analyzing challenges in digital-era implementation, and (3) developing an adaptive framework for Muslim families. Using phenomenological design, researchers conducted in-depth interviews with 20 Muslim parents from diverse backgrounds, selected through purposive sampling. Data analysis employed thematic analysis with NVivo 12 software, ensuring rigorous coding and interpretation. Findings reveal three central practices: role-modeling Prophetic character (85% of participants), narrative-based moral education using Quranic stories (75%), and balanced disciplinary approaches emphasizing mercy (65%). Key challenges include managing digital influences (90%) and reconciling traditional methods with modern parenting needs. The study demonstrates how parents creatively reinterpret Sunnah principles while maintaining theological authenticity, offering practical strategies like technology-integrated Islamic parenting tools. These findings contribute to Islamic family studies by bridging classical scholarship with contemporary child development research, while providing actionable insights for parents, educators, and policymakers. The research implications suggest developing community-based parenting programs and revising Islamic education curricula to address modern challenges while preserving core values.